Visual Exemplars : Biblical Figures in the Art and Literature of Jewish Late Antiquity - Joshowitz, Jill, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2026., 2026)
Between the third to seventh centuries of the common era, Jewish communities throughout the Eastern Mediterranean began to adorn their synagogues with figural illustrations inspired by the Hebrew Bible. Although the Bible had long been the cornerstone of Jewish life, it was only in late antiquity that its patriarchs, prophets, and heroes entered the Jewish visual lexicon. Through careful consideration of the rich history of Jewish biblical interpretation alongside similar motifs in Near Eastern, Greco-Roman, and Christian visual culture, this book challenges the reader to consider the relationship between late antique Jewish biblical art, synagogue rituals, rabbinic teachings, and exemplary paradigms.